2022
DOI: 10.3897/zookeys.1111.72345
|View full text |Cite
|
Sign up to set email alerts
|

Checklist of the caddisflies (Insecta, Trichoptera) of the Upper Midwest region of the United States

Abstract: Five hundred and fifty-two caddisfly species are reported from the Upper Midwest region of the United States, an area that includes 13 states and ~ 2 million km2. Of these, 62 species are reported for the first time from the state of Iowa, 25 from Wisconsin, 18 from South Dakota, 12 from Illinois, five from Indiana, four from North Dakota, four from Minnesota, and one from Nebraska. The Upper Midwest fauna contains nearly 40% of all species known from the United States and Canada, as well as 22 species endemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The known species richness of the Huron Mountains habitats represents > 50% of all 305 species found in Michigan ( Houghton et al 2018 ; Houghton 2020 ) and > 30% of all ~ 550 species found in the Upper Midwest region of the United States (Rasmussen and Morse 2018; Houghton et al 2022 ). The Huron Mountains habitats contained ~ 1.5 × as many caddisfly species (114) as the Black River Ranch of northern Lower Michigan, ~ 2.5 × that of Indiana Dunes National Lakeshore (64), and ~ 3.5 × that of Isle Royale National Park (46), other fairly undisturbed areas of Michigan and northern Indiana sampled with a rigorous effort ( DeWalt and South 2015 ; DeWalt et al 2016 ; Houghton 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The known species richness of the Huron Mountains habitats represents > 50% of all 305 species found in Michigan ( Houghton et al 2018 ; Houghton 2020 ) and > 30% of all ~ 550 species found in the Upper Midwest region of the United States (Rasmussen and Morse 2018; Houghton et al 2022 ). The Huron Mountains habitats contained ~ 1.5 × as many caddisfly species (114) as the Black River Ranch of northern Lower Michigan, ~ 2.5 × that of Indiana Dunes National Lakeshore (64), and ~ 3.5 × that of Isle Royale National Park (46), other fairly undisturbed areas of Michigan and northern Indiana sampled with a rigorous effort ( DeWalt and South 2015 ; DeWalt et al 2016 ; Houghton 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Many of his former mentees submitted articles to this volume, to show their gratitude and respect for Ralph’s life work. The topics he thus influenced range from faunal surveys and checklists ( Cavalcante-Silva et al 2022 ; Chuluunbat et al 2022 ; Houghton 2022 ; Luna-Luna et al 2022 ) and ecological studies ( Houghton et al 2022 ; Ríos-Touma et al 2022 ) to descriptive taxonomy ( Bueno-Soria et al 2022 ; Cavalcante-Silva et al 2022 ; Martins et al 2022 ; Pereira et al 2022 ; Ramírez-Carmona et al 2022 ; Rázuri-Gonzales et al 2022 ) and systematic revisions ( Blahnik and Andersen 2022 ; Sganga et al 2022 ; Thomson et al 2022a , b ).…”
Section: a Much Too Brief CVmentioning
confidence: 99%